Analisis Faktor Penentu yang Mempengaruhi Tingkat Pencemaran Air Sungai di Kabupaten Purbalingga - Nani Fatmawati (Pascasarjana Universitas Jenderal Soedirman, 2022)
Water pollution criteria are likely affecting the occurrence of water pollution indicators. Numerous factors could determine the river water pollution level. These determinant factors will eventually affect the river water pollution countermeasures. Responsibilities to reduce environmental degradation and improve environmental qualities belong to the government and the entire community. It is essential to perform collaborations among the stakeholders since pollution is derived from numerous sectors and activities. This study aims to scrutinize the associations among regulation, activity/business compliance, and public participation both partially and simultaneously towards river water pollution levels in Purbalingga Regency. In this study, 67 respondents were incorporated to take our surveys. The respondents were determined following the purposive sampling technique. Multiple regression analysis was applied through the partial regression coefficient test (τ test) and simultaneous regression coefficient test (F test). The result shows that the R-value of 0,963 could indicate a strong correlation between independent and dependent variables. Then adjust the R2 (R Square) value to 0,854. The activity and business obedience variable show a partially significant effect, which the significance probability level at α = 0.05 towards the level of river water pollution. Both regulation (X1) and activity and business obedience (X2) variables are significantly affecting the river water pollution level (Y), where Fhitung value = 12,707 and Ftabel = 2,74. The conclusion of this study is that the variation of independent variables used in the model could explain as much as 85,40% of the dependent variable variation (river water pollution level). While the rest, 14,60%, is influenced by external variables not applied in this study. On the other hand, the regulation and public participation variables are collectively observed as partially significant effects with a substantial probability level at α = 0.01.